2013
DOI: 10.1021/ol402310b
|View full text |Cite
|
Sign up to set email alerts
|

Urea Activation of Nitrimines: A Mild, Metal-Free Approach to Sterically Hindered Enamines

Abstract: Nitrimines have been identified as impressive starting points for the syntheses of otherwise inaccessible, sterically encumbered enamines. The activation of nitrimines with urea catalysts for reaction with a variety of amines enables the formation of highly substituted enamines in high yield. The reactions benefit from mild, metal-free conditions, high functional group tolerance, and straightforward scale up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…As we became interested in exploiting the attractive reactivity of nitrimines in innovative, metal‐free procedures, we were inspired by their nitrogen‐based nucleophilic exchange reactions 9. To this end, we demonstrated that urea‐activated nitrimines provide access to an impressive array of sterically‐encumbered enamines 10. Our success with nitrimine‐based C–N cross‐coupling reactions prompted us to question the potential utility of nitrimines in more challenging metal‐free C–C cross‐coupling reactions.…”
Section: Methodsmentioning
confidence: 99%
“…As we became interested in exploiting the attractive reactivity of nitrimines in innovative, metal‐free procedures, we were inspired by their nitrogen‐based nucleophilic exchange reactions 9. To this end, we demonstrated that urea‐activated nitrimines provide access to an impressive array of sterically‐encumbered enamines 10. Our success with nitrimine‐based C–N cross‐coupling reactions prompted us to question the potential utility of nitrimines in more challenging metal‐free C–C cross‐coupling reactions.…”
Section: Methodsmentioning
confidence: 99%
“…[9] To this end, we demonstrated that urea-activated nitrimines provide access to an impressive array of stericallyencumbered enamines. [10] Our success with nitrimine-based C-N cross-coupling reactions prompted us to question the potential utility of nitrimines in more challenging metal-free C-C cross-coupling reactions. To our knowledge, the unique reactivity of nitrimines had not been taken advantage of for formal C(sp 2 )-C(sp 2 ) coupling reactions prior to our investigations.…”
mentioning
confidence: 99%